World Development Report 2003 : Sustainable Development in a Dynamic World--Transforming Institutions, Growth, and Quality of Life - World Bank (World Bank, 2012)
Three billion people will be added to the world ' s population over the next 50 years and 2.8 billion people today already live on less than $2 a day-almost all in developing countries. Ensuring these people have access to productive work and a better quality of life is the core development challenge of the first half of this century. Growth could itself be jeopardized over the longer term, unless a transformation of society and the management of the environment are addressed integrally with economic growth. Now in its 25th edition, this year ' s World Development Report examines, over a 50 year period, the relationship between competing policy objectives of reducing poverty, maintaining growth, improving social cohesion, and protecting the environment. The World Development Report 2003 emphasizes that many good policies have been identified but not implemented due to distributional issues and barriers to developing better institutions. The Report reviews institutional innovations that might help overcome these barriers and stresses that ensuring economic growth and improved management of the planet ' s ecosystem requires a reduction in poverty and inequality at all levels: local, national, and international. As in previous years, the report contains an appendix of selected indicators from the World Development Indicators.